Understanding concurrent stimulant use among people on methadone: A qualitative study. (22nd March 2020) - McNeil, Ryan; Puri, Nitsaha; Boyd, Jade; Mayer, Samara; Hayashi, Kanna; Small, Will
Abstract: Introduction and Aims: Opioid‐related overdoses are an epidemic in North America, prompting a greater use of medications for opioid use disorder, such as methadone. Although many people work toward overall drug abstinence while on methadone, a sub‐population of people with and without histories of polysubstance use engage in stimulant use while on methadone treatment. This study explores motivations for concurrent stimulant and methadone use in a street‐involved drug‐using population. Design and Methods: Semi‐structured qualitative interviews were conducted with 39 people on methadone in Vancouver, Canada. Participants were recruited from among the participants in two community‐based prospective cohort studies consisting of HIV‐positive and HIV‐negative people who use drugs. Interview transcripts were analysed using an inductive and iterative approach. Results: Our analysis identified three primary themes. First, participants articulated how stimulants were used to counter the sedating effects of methadone and enable them to engage in daily and survival activities (e.g. income generation). Second, participants described increased stimulant use to compensate for reduced stimulant intoxication while taking methadone. Finally, participants described the desire to achieve intoxication on stimulants once stable on methadone, as their substance use treatment goals did not involve drug abstinence. Discussion and Conclusion: Among a street‐involved drug‐using population in which people do not have abstinence‐based treatment goals, there are several functional reasons to use stimulants concurrently while on methadone. A deeper and more nuanced understanding of substance use motivators may contribute to further research and inform policy and guideline changes that support low threshold and harm reduction‐focused methadone treatment programs and other interventions to reduce drug‐related harms.